RESEARCH METHODS OF PEDAGOGY - Ergasheva Oyjamol Jahongirovna (Galaxy International Interdisciplinary Research Journal, 2021)
This article deals with the general problems which goes around the research methods of modern pedagogy. Methods of pedagogical research are the methods by which pedagogical phenomena are studied and the problems of improvement and progress in the field of education and training are solved. These include both the forms of logical thinking of the experimenter (general methods, algorithms for mental actions) and external actions and procedures that ensure the fulfillment of the experimental tasks.